International organizations amid global crises: analysing role selection and impact through role theory - Panke, Diana; Friedrichs, Gordon (Bristol University Press, 2024)
International organizations have been at the forefront of responding to crises in the twenty-first century, and yet there is little comparative research on how, and how effectively, they have done this. This book fills this gap by exploring what roles international organizations take in response to global crises and to what effect.